Sistem Informasi Akademik Sekolah Menegah Pertama Negeri 12 Palopo - Rusni, R; Dani, Ahmad Ali Hakam; Muhallim, Muhlis (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
This study aims to build and implement a web-based academic information system at SMP Negeri 12 Palopo. The research method used is the system development method with the waterfall model. Data collection techniques using data documentation methods, interviews and observations. The web-based academic information system at SMP Negeri 12 Palopo in its design uses the UML (Unified Modeling Language) development method which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. Logical database design using MySQL and system interfaces. The software used in the design and implementation of the system uses XAMPP as a webserver, PHP, MySQL as a database. The web-based academic information system at SMP Negeri 12 Palopo includes home page registration, student data, teacher data, student grades, lesson schedules, counseling data, student data input, teacher data input, class data input, subject input, lesson schedule input, input value and input data BK. The information system has been tested (test case) in order to obtain an information system that runs well